Processos de Fabricação Aditiva. Oportunidades Emergentes em Arquitetura - João Guilherme Abreu Carvalho (2018)
In the last 20 years, the exploration of Digital Fabrication in Architecture has grown exponentially, complementing consolidation of the digital design processes in the design practice. Among the various technologies, Additive Fabrication (FA) is characterized by a set of processes that selectively add material only where it is needed. This approach constituted its most distinct aspect, allowing the materialization of difficult execution geometries by other methods of production. Motivated by the verification of these capacities, this thesis seeks to study the integration of FA in Architecture. The research begins by understanding the principles, characteristics and operation of the technology, as well as the scopes in which it is being applied. Then, it identifies the challenges and constraints that FA faces in Architecture due to the specific nature and complexity of its product - the building - such as scale, materiality and construction. Following, the thesis describes the assimilation and integration of FA in the Architecture, from the use in the production of models, to the development and application of specific technologies for the construction of buildings. In order to understand the emerging opportunities to influence the discipline of architecture and its processes, the author examines the impact of FA at three levels - representation, construction and materiality - by analyzing several case studies (eg, works developed by Mark Burry, Zaha Hadid, Neri Oxman, Gramazio & Kohler, etc.), and describing the author's practical experience. The conclusion of this research understands that the use of FA can free the architect of certain constraints that frame the design in Architecture, being able to give rise to new expressions and logics of production, but also raise some problems. Thus, the present thesis draws a critical and illustrated reflection on the emergent opportunities of the FA in the practice of Architecture.